Cluster‐Based Crystalline Materials for Iodine Capture - Wang, San‐Tai; Liu, Ya‐Jie; Zhang, Cheng‐Yang; Yang, Fan; Fang, Wei‐Hui; Zhang, Jian (Chemistry : a European journal, 2023)
The treatment of radioactive iodine in nuclear waste has always been a critical issue of social concern. The rational design of targeted and efficient capture materials is of great significance to the sustainable development of the ecological environment. In recent decades, crystalline materials have served as a molecular platform to study the binding process and capture mechanism of iodine molecules, enabling people to understand the interaction between radioactive iodine guests and pores intuitively. Cluster‐based crystalline materials, including molecular clusters and cluster‐based metal‐organic frameworks, are emerging candidates for iodine capture due to their aggregative binding sites, precise structural information, tunable pores/packing patterns, and abundant modifications. Herein, recent progress of different types of cluster materials and cluster‐dominated metal‐organic porous materials for iodine capture is reviewed. Research prospects, design strategies to improve the affinity for iodine and possible capture mechanisms are discussed. Cluster‐based crystalline materials play an important role in the field of iodine host‐guest chemistry. This review summarizes the recent progress of different types of cluster‐based materials (such as cluster‐based MOFs with different cluster nodes, metal‐organic cages, macrocyclic molecules, and cluster composites) for iodine capture. The research status, possible iodine capture mechanisms and prospects of such crystalline materials are discussed.